2009
DOI: 10.1080/15250000802569868
|View full text |Cite
|
Sign up to set email alerts
|

To Share or Not to Share: When Do Toddlers Respond to Another's Needs?

Abstract: The developmental origins of sharing remain little understood. Using procedures adapted from research on prosocial behavior in chimpanzees, we presented 18- and 25-month-old children with a sharing task in which they could choose to deliver food to themselves only, or to both themselves and another person, thereby making it possible for them to share without personal sacrifice. The potential recipient, a friendly adult, was either silent about her needs and wants or made them explicit. Both younger and older t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
224
5
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(257 citation statements)
references
References 41 publications
15
224
5
13
Order By: Relevance
“…Other work shows that give-and-take games, but not mere modeling promote infant sharing [42]. Studies relying on different setups found that even noncostly sharing did not emerge before 25 months and required that the other verbalized her desire [43]. It seems therefore plausible to interpret these earliest instances of sharing as infants being either compliant with an adult's request or as infants perceiving the experimental set-up as part of a give-and-take game activity.…”
Section: A Multidimensional Approach To Early Prosocial Behaviormentioning
confidence: 99%
“…Other work shows that give-and-take games, but not mere modeling promote infant sharing [42]. Studies relying on different setups found that even noncostly sharing did not emerge before 25 months and required that the other verbalized her desire [43]. It seems therefore plausible to interpret these earliest instances of sharing as infants being either compliant with an adult's request or as infants perceiving the experimental set-up as part of a give-and-take game activity.…”
Section: A Multidimensional Approach To Early Prosocial Behaviormentioning
confidence: 99%
“…Children chose randomly in the first two conditions (they received one sweet either way and did not much consider what their partner would get), and they chose the (2,0) allocation in the last condition, to maximize their own gain. Similarly, Brownell, Svetlova, and Nichols (2009) found that 2-year-olds who could share treats with an experimenter tended to choose randomly between a (1,1) and a (1,0) allocation, unless the experimenter explicitly expressed her desire for a treat. As might be expected given these results, investigations of infants' concern about fairness in the allocation of resources have relied mainly on third-party tasks (e.g., Geraci & Surian, 2011;Schmidt & Sommerville, 2011;Sloane, Baillargeon, & Premack, 2012).…”
Section: Do Infants Expect Individuals To Allocate Resources Fairly?mentioning
confidence: 99%
“…By 12 months of age, infants begin to provide helpful information to others [85], at 15 months they will share a toy with an unfamiliar adult [86], and by 18 months they are capable of providing instrumental help; that is, helping another achieve a goal [87]. Moving further into childhood, Brownell et al [88] presented 18-and 25-month-old infants with a task requiring them to pull one of two handles attached to a pair of trays in order to obtain a reward. Pulling one of the handles delivered a loaded tray to the child and to an adult confederate, whereas pulling the alternative handle delivered a loaded tray to the child only.…”
Section: Prosocialitymentioning
confidence: 99%